Estimation of lower flammability limits of C-H compounds in air at atmospheric pressure, evaluation of temperature dependence and diluent effect - Mendiburu, Andres Z. [UNESP]; Carvalho Júnior, João Andrade de [UNESP]; Coronado, Christian R. (Elsevier B.V., 2015)
Estimation of the lower flammability limits of C-H compounds at 25 degrees C and 1 atm; at moderate temperatures and in presence of diluent was the objective of this study. A set of 120 degrees C H compounds was divided into a correlation set and a prediction set of 60 compounds each. The absolute average relative error for the total set was 7.89%; for the correlation set, it was 6.09%; and for the prediction set it was 9.68%. However, it was shown that by considering different sources of experimental data the values were reduced to 6.5% for the prediction set and to 6.29% for the total set. The method showed consistency with Le Chatelier's law for binary mixtures of C H compounds. When tested for a temperature range from 5 degrees C to 100 degrees C , the absolute average relative errors were 2.41% for methane; 4.78% for propane; 0.29% for iso-butane and 3.86% for propylene. When nitrogen was added, the absolute average relative errors were 2.48% for methane; 5.13% for propane; 0.11% for iso-butane and 0.15% for propylene. When carbon dioxide was added, the absolute relative errors were 1.80% for methane; 5.38% for propane; 0.86% for iso-butane and 1.06% for propylene. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Lower flammability limits; Estimation; Temperature dependence; Diluent effect